The role of total pancreatectomy with islet autotransplantation in the treatment of chronic pancreatitis: a report from the International Consensus Guidelines in chronic pancreatitis - Abu-El-Haija, Maisam; Hackert, Thilo; Neoptolemos, John P.; Anazawa, Takayuki; Beilman, Gregory J; Besselink, Marc G; Del Chiaro, Marco; Demir, Ihsan Ekin; Dennison, Ashley R; Dudeja, Vikas; Freeman, Martin L; Friess, Helmut; et al. (Pancreatology, 2020)
Background - Advances in our understanding of total pancreatectomy with islet autotransplantation (TPIAT) have been made. We aimed to define indications and outcomes of TPIAT. - Methods - Expert physician-scientists from North America, Asia, and Europe reviewed the literature to address six questions selected by the writing group as high priority topics. A consensus was reached by voting on statements generated from the review. - Results - Consensus statements were voted upon with strong agreement reached that (Q1) TPIAT may improve quality of life, reduce pain and opioid use, and potentially reduce medical utilization; that (Q3) TPIAT offers glycemic benefit over TP alone; that (Q4) the main indication for TPIAT is disabling pain, in the absence of certain medical and psychological contraindications; and that (Q6) islet mass transplanted and other disease features may impact diabetes mellitus outcomes. Conditional agreement was reached that (Q2) the role of TPIAT for all forms of CP is not yet identified and that head-to-head comparative studies are lacking, and that (Q5) early surgery is likely to improve outcomes as compared to late surgery. - Conclusions - Agreement on TPIAT indications and outcomes has been reached through this working group. Further studies are needed to answer the long-term outcomes and maximize efforts to optimize patient selection.